First experiences in the implementation of biometric technology to link data from Health and Demographic Surveillance Systems with health facility data - Adwoa Serwaa-Bonsu; Abraham J. Herbst; Georges Reniers; Wilfred Ijaa; Benjamin Clark; Chodziwadziwa Kabudula; Osman Sankoh (Taylor & Francis Group, 2010)
Background: In developing countries, Health and Demographic Surveillance Systems (HDSSs) provide a framework for tracking demographic and health dynamics over time in a defined geographical area. Many HDSSs co-exist with facility-based data sources in the form of Health Management Information Systems (HMIS). Integrating both data sources through reliable record linkage could provide both numerator and denominator populations to estimate disease prevalence and incidence rates in the population and enable determination of accurate health service coverage. Objective: To measure the acceptability and performance of fingerprint biometrics to identify individuals in demographic surveillance populations and those attending health care facilities serving the surveillance populations. Methodology: Two HDSS sites used fingerprint biometrics for patient and/or surveillance population participant identification. The proportion of individuals for whom a fingerprint could be successfully enrolled were characterised in terms of age and sex. Results: Adult (18–65 years) fingerprint enrolment rates varied between 94.1% (95% CI 93.6–94.5) for facility-based fingerprint data collection at the Africa Centre site to 96.7% (95% CI 95.9–97.6) for population-based fingerprint data collection at the Agincourt site. Fingerprint enrolment rates in children under 1 year old (Africa Centre site) were only 55.1% (95% CI 52.7–57.4). By age 5, child fingerprint enrolment rates were comparable to those of adults. Conclusion: This work demonstrates the feasibility of fingerprint-based individual identification for population-based research in developing countries. Record linkage between demographic surveillance population databases and health care facility data based on biometric identification systems would allow for a more comprehensive evaluation of population health, including the ability to study health service utilisation from a population perspective, rather than the more restrictive health service perspective.